Development of the Outcome Based Education (OBE) Concept in the Entrepreneurship Course - Harmaman, Harmaman; Musriani, Musriani (International Journal of Economics Development Research (IJEDR), 2024)
Currently, the transformation of higher education in Indonesia has established a policy called Independent Campus. In supporting this, universities need to prepare learning tools that are reconstructive, flexible and adaptable according to the needs of the world of work. Of course, this is closely related to the concept of Outcome Based Education (OBE). Researchers will develop learning tools for the Entrepreneurship Course in the Physical Education study program at the Muhammadiyah Sorong Education University. The Entrepreneurship course is one of the university's priority programs in preparing graduates with an entrepreneurial spirit. The aim of this research is to improve student learning outcomes and make the OBE concept a role model in the development of RPS within the Sorong Muhammadiyah University of Education. The research method used is 4D research and development, namely the Define stage, Design stage, Develop stage and Disseminate stage. The research results showed that student learning outcomes increased as measured using the pretest with a percentage of 40.67% and posttest with a percentage of 80.67%. Furthermore, the N-gain analysis obtained an average of 0.67% which is interpreted as the effectiveness of applying the OBE concept in Entrepreneurship courses in the medium category, so it can be concluded that the RPS which has been developed into an outcome based education concept is suitable for application in Entrepreneurship learning in the Physical Education Study Program Sorong Muhammadiyah University of Education.